Integration of Women into the Labor Market in Azerbaijan: A Comprehensive Review - Mammadova, Ulviyya (Dunakavics, 2024)
The integration of women into the labor market is a critical issue that influences not only individual economic empowerment but also broader socio-economic development. In Azerbaijan, the participation of women in the workforce has been a topic of considerable attention among policymakers, researchers, and international organizations. Despite significant progress in educational attainment among women, their engagement in the labor market remains disproportionately low compared to men. This disparity highlights the multifaceted barriers that women face in securing and sustaining employment, ranging from socio-cultural norms to structural and policy-related obstacles. Azerbaijan, like many other countries, has witnessed substantial socio-economic transformations over the past few decades. These changes have brought about new opportunities and challenges for women's economic participation. Traditional gender roles, which assign primary caregiving responsibilities to women, continue to influence their ability to engage fully in paid employment. Additionally, the lack of supportive infrastructure, such as affordable childcare and flexible working arrangements, exacerbates these challenges, making it difficult for women to balance work and family commitments. Efforts to improve gender equality in the labor market are essential for fostering inclusive economic growth and development. Various studies have highlighted the importance of addressing both cultural and structural barriers to enhance women's labor market participation. International organizations, including the European Union, have been actively supporting initiatives aimed at promoting gender equality and empowering women in Azerbaijan. These efforts underscore the need for comprehensive strategies that address the root causes of gender disparities and promote an enabling environment for women's economic participation.